2014
DOI: 10.1002/cpdd.169
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ and multiple‐dose pharmacokinetic studies of tramadol immediate‐release tablets in children and adolescents

Abstract: In these combined analyzes from 3 open-label, phase-1 studies, the pharmacokinetic profile of tramadol and its metabolite (M1) following administration of tramadol immediate-release (IR) tablets in children and adolescents, 7-16 years old (studies 1 and 2: n = 38; study 3: n = 21) with painful conditions following single oral dose of tramadol IR (25-100 mg) (studies 1 and 2) or multiple oral doses of tramadol IR tablets every 6 hours for 3 days (study 3) were compared with that of healthy adults following simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The PK profiles of tramadol and its metabolite M1 in children and adolescents, in single‐dose and multiple‐dose studies of immediate‐release tramadol, were low—particularly in those with a lower body weight—compared with the adult PK profile, as reported in a recent publication . The results from the current 2 studies corroborated the previously reported findings that the PK profiles resulted in a lower exposure to tramadol and its M1 metabolite in 7‐ to 11‐year‐old children.…”
Section: Discussionmentioning
confidence: 99%
“…The PK profiles of tramadol and its metabolite M1 in children and adolescents, in single‐dose and multiple‐dose studies of immediate‐release tramadol, were low—particularly in those with a lower body weight—compared with the adult PK profile, as reported in a recent publication . The results from the current 2 studies corroborated the previously reported findings that the PK profiles resulted in a lower exposure to tramadol and its M1 metabolite in 7‐ to 11‐year‐old children.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of the study data using body weight adjusted and dose‐normalized pharmacokinetic parameters clearly showed that the pediatric age group tended to have differential pharmacokinetic behavior of tramadol compared with adults . The apparent oral clearance of tramadol was faster in the pediatric age group (13.14 mL/min/kg) compared with adults (9.47 mL/min/kg).…”
mentioning
confidence: 97%
“…Because of ethical considerations the pediatric population in this investigation appeared to be less homogenous . The authors have emphasized caution in the interpretation of the data to enable the design of future clinical pharmacology studies because some of the children/adolescents who participated in this study had a history of surgical operation and/or had a history of painful conditions …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tramadol is rapidly absorbed after oral administration, with an absolute bioavailability of approximately 70%, irrespective of concomitant food intake . Tramadol is extensively metabolized in the liver, resulting in many phase I and II metabolites.…”
mentioning
confidence: 99%